Representasi Sejarah Masyarakat Lasem, Rembang, Jawa Tengah Dalam Syair Laesan - Devi Rahma Aulia; Maulfi Syaiful Rizal (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2026)
This research highlights the poems and songs that accompany the laesan dance, with a focus on analyzing the lyrics of laesan poems. Broadly speaking, laesan is a dance movement art originating from Lasem, Rembang Regency, Central Java. This type of research is qualitative with descriptive and literature methods. In analyzing laesan poems, Alan Swingewood's literary sociology theory is used as an analytical tool. Data in this study was collected through in-depth interviews, observations, and documentation. This study found that laesan poems, as part of literature as a whole, play a role in recording and summarizing the history of Lasem and the dynamics of its community. Thus, laesan poems can be used as one of the sources for historical documentation to complement the historical treasury of Lasem city. In addition, laesan poems also reflect the plurality of its society, the maritime glory of Lasem in the past, up to Lasem’s history as a smuggling center.